MORPHOLOGY OF GIANT MUDSKIPPER FISH (Periophthalmodon schlosseri) - Selamat ariyadin; Rahman Karnila; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThe giant mudskipper fish is a type of non-economic fish found in muddy river mouths. This study aimed to determine the percentage of the body parts of the giant mudskipper fish. The method used in this research was exploratory in which the data is analyzed descriptively. The method of determining the body parts of the fish is done by separating the parts of the fish consisting of the flesh, internal organs (intestines, liver, pancreas, swim bladder,heart), skin and scales. The percentages of the cloth are calculated as the percentage of the body parts of the giant mudskipper fish. The results of the calculation of the body parts of the giant mudskipper fish showed that the percentage of meat was 25%, viscera 5%, skin, and scales 70%. The giant mudskipper fish had a fat content of 0.48% body weight. The proportion of the most of the giant mudskipper fish was the skin and scales of 70%. Keywords: Fat content, Morphology of giant mudskipper fish, Percentage